Optically Visible Phase Separation between Mott‐Hubbard and Charge‐Density‐Wave Domains in a Pd‐Br Chain Complex. Issue 2 (16th February 2016) - Yoshida, Takefumi; Takaishi, Shinya; Iguchi, Hiroaki; Okamoto, Hiroshi; Tanaka, Hisaaki; Kuroda, Shin‐ichi; Hosomi, Yuka; Yoshida, Shoji; Shigekawa, Hidemi; Kojima, Tatsuhiro; Ohtsu, Hiroyoshi; Kawano, Masaki; et al.
Abstract: We synthesized a bromo‐bridged Pd complex, which underwent as lowering the temperature a charge‐density‐wave (CDW) to Mott‐Hubbard (MH) phase transition, as confirmed by using X‐ray diffraction analysis, ESR, FT‐IR and Raman spectroscopies. The complex showed a phase‐separation phenomenon with a striped pattern over a wide temperature range, and domain propagation was observed using an optical microscope. Moreover, we observed changes in the local electronic state accompanying the phase transition by using scanning tunneling microscopy (STM) Abstract : Charge–transfer phase transition and phase separation : We synthesized a bromo‐bridged Pd complex, which underwent a charge‐density‐wave (CDW) to Mott‐Hubbard (MH) phase transition. The complex showed a phase‐separation phenomenon with a striped pattern over a wide temperature range.